2020
DOI: 10.1016/j.heliyon.2020.e04414
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural factors affecting drive for muscularity among male college students in Malaysia

Abstract: Compared with females, little research on muscularity and the sociocultural influences on this domain has been conducted with males in non-Western societies. The current study explored these sociocultural predictors of drive for muscularity among Malaysian male college students, specifically in terms of ethnicity and exposure to media (i.e., Internet and social media). In total, 166 male college students from two universities in Kuala Lumpur were asked to rate the questionnaires as to muscularity-oriented atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…No scales on weight- or muscularity-related stigmatizing beliefs exist to our knowledge. The vast majority of data on this topic originated from the United States [ 48 ], and other Western countries [ 49 51 ]. Global studies with cross-cultural comparisons remain scarce [ 52 54 ], in spite of being identified as a key future research direction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…No scales on weight- or muscularity-related stigmatizing beliefs exist to our knowledge. The vast majority of data on this topic originated from the United States [ 48 ], and other Western countries [ 49 51 ]. Global studies with cross-cultural comparisons remain scarce [ 52 54 ], in spite of being identified as a key future research direction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%